Skrining Fitokimia Ekstrak Daun Mimba (Azadirachta indica Juss) dan Kemangi (Ocimum sanctum L.) dan Evaluasinya Sebagai Hair Tonic Spray - Irwan, Andi Annisa Anastasya; Dzakiyah, Ainun; Angriani, Yuni; Asri, Fitriani; Khalid, Davi Rahmat; Purnamasari, Vina; Yuliana, Dewi (Faculty of Pharmacy, Universitas Muslim Indonesia, 2024)
A phytochemical screening of Neem (Azadirachta indica Juss) and Holy Basil (Ocimum sanctum L) leaf extracts has been conducted, along with a hair tonic spray formulation. The aim of this research is to determine the chemical constituents of Neem and Holy Basil leaf extracts and formulate them into a hair tonic spray. The study included tests for flavonoids, tannins, alkaloids, steroids, and saponins in both Neem and Holy Basil extracts, as well as an evaluation of the stability of the hair tonic spray formulation. The research findings revealed that the Neem and Holy Basil extracts contain flavonoids, tannins, alkaloids, steroids, and saponins. The formulation was evaluated through organoleptic assessments, homogeneity tests, pH measurements, bulk density, and viscosity assessments, all of which Evaluation met the requirements established for a hair tonic spray.